Introducing Management Accounting Techniques Through The Ages And Their Impact On Arab Enterprises - Kerdouci, Mohammed (جامعة الوادي - University of Eloued, 2021)
This study aimed to provide a historical overview of the introduction of management accounting techniques through the ages, and to know their impact on the establishments used for them and the factors that determine the change in the form of management accounting, and the extent to which these modern mechanisms are practiced and included in Arab establishments, especially since these mechanisms have become a common topic in the modern industrial environment.After the old technologies failed to comply with the requirements of the times (efficiency, effectiveness, flexibility, speed ...), as the descriptive analytical approach was relied upon, through historical literature as well as modern research in the field of study. Among the results of this study, the practice of these modern technologies is issued in the countries of the Arab Mashreq, on top of which is the State of Palestine, followed by Syria, Jordan, and Iraq, where the activity-based cost system is the most applied, and in the Maghreb, it is completely non-existent, as its application is limited to only those who During scientific research.
مقال
Keywords: Management accounting ; Accounting administration ; Modern mechanisms ; Modern environment ; Global competition